VD_FINDINFO Décision / 2016 / 931 vom 27. Dezember 2016 - VD Tribunal cantonal (2016)
DÉTENTION PROVISOIRE, RISQUE DE RÉCIDIVE, RISQUE DE COLLUSION | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)